A millifluidic bioreactor allows the long term culture of primary lymphocytes or CD34+ hematopoietic cells while allowing the detection of tumorigenic expansion - Ritter, Paolo; Oliveto, Stefania; Cordiglieri, Chiara; Fasciani, Alessandra; Di Buduo, Christian Andrea; della Volpe, Lucrezia; Bocconi, Alberto; Conci, Claudio; Miguel, Carolina Paula; Di Micco, Raffaella; Balduini, Alessandra; Raimondi, Manuela Teresa; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Long-term culture of primary lymphocytes and hematopoietic stem and progenitor cells (HSPCs) is pivotal to their expansion and study. Furthermore, genetic engineering of the above-mentioned primary human cells has several safety needs, including the requirement of efficient in vitro assays for unwanted tumorigenic events. In this work, we tested and optimized the Miniaturized Optically Accessible Bioreactor (MOAB) platform. The MOAB consists of a millifluidic cell culture device with three optically-accessible culture chambers. Inside the MOAB, we inserted a silk-based framework that resembles some properties of the bone marrow environment and cultivated in this device either CD4 + T lymphocytes isolated from healthy donor buffy coat or cord blood-derived hematopoietic CD34 + cells. A fraction of these cells is viable for up to three months. Next, we tested the capability of the MOAB to detect tumorigenic events. Serial dilutions of engineered fluorescent tumor cells were mixed with either CD4 + or CD34 + primary cells, and their growth was followed. By this approach, we successfully detected as little as 100 tumorigenic cells mixed with 100,000 primary cells. We found that non-tumorigenic primary cells colonized the silk environment, whereas tumor cells, after an adaptation phase, expanded and entered the circulation. We conclude that the millifluidic platform allows the detection of rare tumorigenic events in the long-term culture of human cells.